Pear rust: peculiarities of pathogen biology measures for control and profilactic - A. Cherniy (Карантин і захист рослин)
Goal. To carry out an analysis of the spread, peculiarities of the biology of the rust pathogen — the fungus Gymnosporangium sabinae (Dicks.) Wint., the dynamics of the disease, control measures.